The Uneasy Promise of Deposit Insurance: Financial Globalization and the Protection of Savers. (August 2013) - Zimmermann, Hubert
Institutionalized guarantees of saving deposits are, in addition to financial supervision and the central banks' role as lender of last resort, traditional key instruments of states to ensure the economic security of individuals and the stability of financial systems. As such, they are a crucial fundament of modern political economies. Financial globalization and the financialization of savings have increasingly undermined these safety nets. This article argues that these phenomena have not only led to a new precariousness of individual provisions for the future, but also resulted in a flurry of activities by states to bolster existing arrangements to protect savers. Such efforts will be limited in their effectiveness as long as substantial variations exist among different national protective systems. I argue that such differences can partly be explained by the embeddedness of deposit protection systems in different varieties of financial capitalism. This institutionalist explanation has to be supplemented by a theory of interest group influence which emphasizes how concentrated interests manage to push through their preferences and block reform efforts in the global regime of protecting savers. These entrenched interests make it unlikely that current harmonization efforts, as advanced by the Financial Stability Board and the European Union, will be successful.